Cultural challenges in translating Tayeb Salih’s novel Season of Migration to the North (1969) from Arabic into English : a comparative and analytical study with a focus on metaphors and similes - Marais, Renée (University of Pretoria, 2021)
Dissertation (MA (Applied Language Studies))--University of Pretoria, 2020.